2008
DOI: 10.1097/ccm.0b013e318168f649
|View full text |Cite
|
Sign up to set email alerts
|

The costs and cost-effectiveness of an integrated sepsis treatment protocol

Abstract: In patients with septic shock, an integrated sepsis protocol, although not cost-saving, appears to be cost-effective and compares very favorably to other commonly delivered acute care interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 31 publications
4
61
0
1
Order By: Relevance
“…However, the estimated ICER (4,435 euros per LYG) was significantly lower than the commonly accepted threshold of 30,000 euros per LYG used in Spain [31]. Moreover, our results are in agreement with those of a recent study conducted in the US that showed that a protocol similar to the SSC protocol is a cost-effective alternative to the usual care of severe sepsis with an ICER of 11,274 dollars per LYG (8,906 euros per LYG) [17]. Another similar recent study, also conducted in the US, showed even better results as the sepsis protocol both improved mortality and reduced costs [33].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the estimated ICER (4,435 euros per LYG) was significantly lower than the commonly accepted threshold of 30,000 euros per LYG used in Spain [31]. Moreover, our results are in agreement with those of a recent study conducted in the US that showed that a protocol similar to the SSC protocol is a cost-effective alternative to the usual care of severe sepsis with an ICER of 11,274 dollars per LYG (8,906 euros per LYG) [17]. Another similar recent study, also conducted in the US, showed even better results as the sepsis protocol both improved mortality and reduced costs [33].…”
Section: Discussionsupporting
confidence: 90%
“…We then adjusted these life expectancies using the estimated reduction rate for sepsis survivors, 0.51, suggested by Quartin et al [14]. This approach was recently used to assess the cost-effectiveness of severe sepsis interventions [15][16][17]. LYGs were discounted at an annual rate of 3%.…”
Section: Life-years Gained and Quality-adjusted Life Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…By combining quantitative and qualitative data, the most efficient and cost‐effective solution for a clinical problem can be evaluated11, 12, 13. Those outcomes help decision‐makers (NHS funding) to derive evidence‐based decisions on long‐term costs savings and, importantly, individual and societal wellbeing14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%